2019
DOI: 10.1016/j.jped.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep quality on academic performance is mediated by Internet use time: DADOS study

Abstract: The association between sleep quality and academic performance in adolescents is mediated by time of Internet use. Overall, reducing Internet use in adolescents could be an achievable intervention for improving sleep quality, with potentially positive effects on academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 24 publications
1
18
0
4
Order By: Relevance
“…In relation to sleep quality, more adolescents from Seville and Tartu (51%) reported poor perceived sleep quality (PSQI ≥ 5) than did those from Reykjavik (41%). Our data agrees with similar studies in the participating cities [64,[74][75][76][77], as well as those reported in a longitudinal study that examined trends in the difficulty of sleeping in adolescents over 12 years [78].…”
Section: Sleep Qualitysupporting
confidence: 93%
“…In relation to sleep quality, more adolescents from Seville and Tartu (51%) reported poor perceived sleep quality (PSQI ≥ 5) than did those from Reykjavik (41%). Our data agrees with similar studies in the participating cities [64,[74][75][76][77], as well as those reported in a longitudinal study that examined trends in the difficulty of sleeping in adolescents over 12 years [78].…”
Section: Sleep Qualitysupporting
confidence: 93%
“…The articles were mostly cross-sectionally designed, as expected, due to the epidemiological and observational characteristics of the studies about lifestyle behaviors in this population [ 6 , 50 , 55 ]. Additionally, 28 studies were considered to have presented strong evidence, in accordance with the criteria of the risk of bias assessment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in adolescents, the duration of television viewing was inversely associated with composite scores (effect size = −0.19; 95% CI, −0.30 to −0.07) and mathematics (effect size = −0.21; 95% CI, −0.26 to −0.15). In addition, the duration of video game play- Keith et al, 43 1986 Fetler, 34 1984 Ferguson 33 2011Cooper et al, 29 1999 Caldas and Bankston, 27 1999, white students Caldas and Bankston, 27 1999, black students Adelantado-Renau et al, 25 Sensitivity analyses suggested that the pooled effect size estimation for the association between television viewing and language was slightly modified when data from several studies were removed, with effect size ranging from −0.21 to −0.13. 25,34,55,57,59,60,67 The pooled effect sizes for the remaining associations were not modified by the one-by-one removal of the included cohorts (eTable 5 in the Supplement).…”
Section: Meta-analysismentioning
confidence: 99%